Extracellular vesicles and the extracellular matrix: a new paradigm or old news?. (14th October 2020) - Lewin, Samuel; Hunt, Stuart; Lambert, Daniel W.
Abstract : Extracellular vesicles (EV) are implicated in a variety of functions affecting the extracellular matrix (ECM), including matrix degradation, cross-linking of matrix proteins and matrix calcification. These processes are important in many physiological contexts such as angiogenesis and wound healing, and dysregulation of ECM homeostasis contributes to a wide range of diseases including fibrosis, cancer and arthritis. Most studies of EV have focussed on their roles in cell:cell communication, but EV can exist as integral components of the ECM. By far the most well-characterised ECM-resident EV are matrix vesicles (MV) in bone, but the broader role of EV in the ECM is not well understood. This review will explore what is known of the roles of EV in the ECM and will also highlight the similarities and differences between MV and other EV.